Antecedents and Consequences of User Satisfaction in Measurement of The Successful Implementation of Institution Level Financial Application System (SAKTI) - Fathmaningrum Erni Suryandari; Intani Ezadhea Cherry Aura (SHS Web of Conferences)
This research aims to measure the level of success in implementing SAKTI in the Work Unit Office which is one of the vertical units of the Directorate General of Treasury, Ministry of Finance. The procedure is carried out by analysing the factors that influence the success of information system implementation based on TAM theory and referring to the [1] information system success model. The type of data in this research is primary data using a questionnaire method. The subjects of this research are implementing employees who use the SAKTI application in the Special Region of Yogyakarta Province. The sampling method in this research used a purposive sampling technique. This research derived four hypothesis which were tested using the SEM-PLS analysis tool via the smartPLS v4.0 application. The results of this research show that information quality and service quality have a positive effect on user satisfaction, while system quality has no effect on user satisfaction. Then user satisfaction has a positive effect on net benefits.